ABAMECTIN APPLICATION INTERVALS ON SUPPRESSION Meloidogyne enterolobii IN TOMATO - Romano, M. J.; Correia, E. C. S. S.; Monteiro, R. N. F.; Fontana, L. F.; Silva, D. P. (Revista Brasileira de Engenharia de Biossistemas, 2016)
Tomato is one of the major vegetable crops grown in Brazil. In recent decades, with the growth of cultivation in a protected environment also intensified phytosanitary problems, among which, infestation by nematodes of various species. The objective of this study was to determine the effect of different abamectin application ranges in tomato crop aimed at suppressing M. enterolobii. The experiment was conducted in a greenhouse in the municipality of Lupércio/SP. The experimental design was completely randomized with eight treatments and four replications. Applications were conducted according to the manufacturer’s recommendation (1 mL of the commercial product/1L H2O) using all treatments standard dosage of 50 mL of the solution. After 60 days of inoculation of the nematode, they proceeded to the plant height assessments, fresh weight of shoot and root gall index and egg masses and the nematode reproduction factor. The results showed that the T1, T2 and T3 acted preventively, as were applied directly to the tray three days before the transplant, featuring the most efficient in the management of this species of Meloidogyne, with a significant difference when compared with other treatments.